Land Use Changes and Morphological Evolution of Man-Made Lake System in Yamoussoukro, Côte d'Ivoire - LAZARE, Kouassi Kouakou; ANDRÉ, N’Guessan Kouamé; ALEXIS, Brou Loukou; TRAORÉ, Karim Sory (Current Research on Geography, Earth Science and Environment Vol. 1, 2025)
The man-made lakes of Yamoussoukro were designed in the 1970s to embellish the city. The rapid siltation of the lakes of Yamoussoukro is due to sediment transport, linked to erosion in the watershed due to human activities, including urbanisation and agriculture. On the other hand, accelerated eutrophication is due to the discharge of untreated wastewater and solid waste into the lakes and the lack of a lake monitoring and maintenance plan. The objective of this study is to evaluate the dynamics of land use and the evolution of the morphology of the man-made lake system of Yamoussoukro. The municipality of Yamoussoukro encloses ten man-made lakes which have been designed for the embellishment of the city and the regulation of rainwater. However, despite their ecological, tourist and economic importance, human activities in the lake watersheds are causing a deterioration in water quality and siltation of the lakes’ reservoirs. A study of land use was carried out through an analysis of satellite images from 1988 to 2018, coupled with a sedimentological study to assess the dynamics of land use and its impacts on the man-made lake system of Yamoussoukro. Land use and bathymetric maps show that the watershed suffered a significant degradation from 1988 to 2018. The granulometric and mineralogical analyses carried out on the sediments collected during this study showed that the sediments that fill the bottom of the lakes are made up of mud, fine sand and medium sand. The resulting erosion, wastewater and household waste dumped into the lakes through a lack of adequate sanitation systems accelerate the deterioration of the lake environment. The siltation and eutrophication of the Yamoussoukro lakes are very noticeable and pronounced. Hence, the gradual disappearance of these water bodies is being witnessed. The restoration of the integrity of the lakes and the implementation of a monitoring plan for the lake environments of Yamoussoukro city are necessary to embellish the city, improving the quality of the environment, developing tourism and preserving biodiversity.